#### Answer

$a_{5}=a_{1}\times r^{4}=3\times \left( -\dfrac {3}{4}\right) ^{4}=\dfrac {-243}{256};$
$a_{n}=a_{1}\times r^{n-1}=3\times \left( \dfrac {-3}{4}\right) ^{n-1}$

#### Work Step by Step

$r=\dfrac {\dfrac {-81}{64}}{\dfrac {27}{16}}=\dfrac {\dfrac {27}{16}}{\dfrac {-9}{4}}=\dfrac {\dfrac {-9}{4}}{3}=-\dfrac {3}{4};a_{1}=3\Rightarrow a_{5}=a_{1}\times r^{4}=3\times \left( -\dfrac {3}{4}\right) ^{4}=\dfrac {-243}{256};a_{n}=a_{1}\times r^{n-1}=3\times \left( \dfrac {-3}{4}\right) ^{n-1}$